The Challenges of Smart Tourism: a Case of Bucharest - Sabou, Gabriel-Cristian; Maiorescu, Irina (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
The advancement of technology makes smart devices and their applications ever more popular and complex. Tourism is an area where varied and numerous services are required, hence this diversity resulted in a multitude of smart applications and smart systems designed to enhance tourist‘s satisfaction. The present paper investigates the concept of Smart Tourism in the scientific literature and how it can be applied for mobile applications, with particular focus on the most popular Smart Tourism apps for Bucharest. Following the analysis of these apps according to the theoretical framework applied, recommendations for improvement of Bucharest Smart Tourism mobile applications are provided.